Nonlinear control of a pneumatic actuator based on a dynamic friction model - Bo Tran, Xuan (Strojniški vestnik, 2021)
This paper presents a new controller for the position of a pneumatic actuator. The controller is designed based on the multiple-surface sliding control method in combination with a frictional compensator. The multiple-surface sliding control method is applied to deal with the nonlinear characteristics of the pneumatic system, and the frictional compensator is applied to compensate for the friction force in the pneumatic actuator. The friction force is estimated based on a dynamic friction model (the LuGre model). Both simulation and experimental studies are done to evaluate the new controller. The evaluation results indicate significant improvement in the tracking position error of the new controller comparing to the multiple-surface sliding controller without friction compensation and other nonlinear controllers.
Keywords: dinamični model trenja; dynamic friction model; friction compensation; kompenzacija trenja; nelinearno vodenje; nonlinear control; pneumatic actuator; pnevmatski valji